PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. BPR BKK PATI (PERSERODA) DI PATI - Isti Mayasari (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
Employees are a very valuable company asset that must be managed properly by the company in order to make an optimal contribution. At work employees must be able to feel comfortable, be valued, be able to develop all the potential they have, so employees could more focus and concentrate to do their own job also reach out their work performance achievements. The population in this research is 33 employees of PT. BPR BKK Pati (Perseroda) and the sample was 33 peoples, so this research is called a census. The analytical tools used are multiple regression, t-test and the coefficient of determination is processed by the SPSS program. The results of the analysis show that individual characteristics have a positive influence on the work performance of PT. BPR BKK Pati employees. The work environment also has a positive influence on the work performance of PT. BPR BKK Pati employees.